Avaliação da segurança e genotoxicidade do chá de Alpinia zerumbet (pers.) Burrt & Smith em voluntários sadios - Santana, Ana Paula Macêdo (2009)
Alpinia zerumbet, popularly known as Colonia in the Northeast of Brazil, is a medicinal plant widely used in the popular medicine as a tea, being traditionally used to treat arterial hypertension. The objective of this study was to evaluate the safety and genotoxic potential of the A. zerumbet tea in healthy volunteers. Clinical trial consisted of a double-blind study, placebo controlled, randomized and parallel, with 36 adult volunteers (18 men and 18 women), which were randomly distributed in two groups: Colonia, consisted of 24 volunteers, and Placebo, consisted of 12 subjects. The volunteers were treated for 28 consecutive days, with 540 mL of Colonia or Placebo tea. Clinical and laboratorial evaluations were performed during the pre-study and treatment, as well as during the closure of the study. The genotoxicity of the Colonia tea was investigated by the comet assay. The body mass index (BMI) was 25.300±2.918 Kg/ cm2 for the Colonia group in the pre-study and 25.289±2.965Kg/ cm2 in the end of the study. For the Placebo group, BMI was 25.179±2.564 in the pre-study and 24.961±2.409 after the study. The blood, liver, kidney and metabolic functions were analyzed before, during (14th and 28th day) and after the study by the evaluation of laboratorial exams, which did not evidence signs of toxicity. Headache, sleepiness, abdominal pain, vomit, flatulence and polyuria were the adverse events attributed to the ingestion of the tea in both groups. The comet assay did not show damage in peripheral lymphocytes of the volunteers treated with the Colonia tea (p<0.05). The clinical toxicology and genotoxicity studies did not evidence any toxicity in the volunteers treated for 28 consecutive days with the Colonia tea.